Loans in Colonial and Modern Nahuatl : A Contextual Dictionary. - Brylak, Agnieszka. (Trends in Linguistics. Documentation [TiLDOC] Series, 2020)
Volumes in the Trends in Linguistics. Documentation series focus on the presentation of linguistic data. The series addresses the sustained interest in linguistic descriptions, dictionaries, grammars and editions of under-described and hitherto undocumented languages. All world-regions and time periods are represented.